Improving School Leadership The Promise of Cohesive Leadership Systems - Augustine, Catherine H. (RAND Corporation, 2009)
This study documents actions of Wallace Foundation grantees to create more-cohesive policies and initiatives to improve instructional leadership in schools; describes how states and districts have worked together to forge such policies and initiatives; and examines the hypothesis that cohesive systems improve school leadership. Such efforts appear to be a promising approach to developing school principals engaged in improving instruction.